A six-parameter Iwan model and its application. (February 2016) - Li, Yikun; Hao, Zhiming
Abstract: Iwan model is a practical tool to describe the constitutive behaviors of joints. In this paper, a six-parameter Iwan model based on a truncated power-law distribution with two Dirac delta functions is proposed, which gives a more comprehensive description of joints than the previous Iwan models. Its analytical expressions including backbone curve, unloading curves and energy dissipation are deduced. Parameter identification procedures and the discretization method are also provided. A model application based on Segalman et al.׳s experiment works with bolted joints is carried out. Simulation effects of different numbers of Jenkins elements are discussed. The results indicate that the six-parameter Iwan model can be used to accurately reproduce the experimental phenomena of joints. Highlights: A six-parameter Iwan model for bolted joint is proposed. Analytical expressions of the six-parameter Iwan model are deduced. Parameter identification procedure and discretization method are provided. The presented model is able to reproduce experimental results of bolted joints.